The impact of thermal mass on building energy consumption: A case study in Al Mafraq city in Jordan. Issue 1 (1st January 2020) - Sharaf, Firas
Abstract: This research discusses the usage of thermal mass of construction materials to produce comfortable thermal indoor environment and to reduce energy consumption used for cooling and heating. What motivated this research is the disappearance of traditional construction methods and materials, such as thick stone and clay walls. Stone is used as a coating material in new buildings, but little attention is given to its significant thermal properties. These construction methods which are ideal to perform as thermal masses are becoming extinct in modern buildings. To achieve this aim a test of thermal mass efficiency is conducted on a case study building which consists two parts of different thermal mass under same climate condition in Jordan. Indoor temperatures of two rooms; one with clay walls; and a second room with concrete brick walls are measured at day and night times in summer and winter. Findings indicate that in hot and cold climates, the temperature inside the room of clay walls are kept within the human comfort zone, unlike the temperature in the room with concrete walls, which was not in the human comfort zone by 5°C. Results are recorded and analyzed to draw useful insights and recommendations. This research concludes that construction materials of high thermal mass, such as clay-bricks, significantly keep the indoor environment within the human thermal comfort zone. Thus, the energy required for maintaining the thermal comfort of the room is greatly reduced.